A comprehensive study on the seakeeping performance of high speed hybrid ships by 2.5D theoretical calculation and different scaled model experiments. (15th July 2018) - Jiao, Jialong; Sun, Shuzheng; Li, Jide; Adenya, Christiaan Adika; Ren, Huilong; Chen, Chaohe; Wang, Dongjiao
Abstract: In this paper, seakeeping performance of vessels is comparatively investigated by means of improved 2.5D theoretical calculation, small-scale model towing tank test and large-scale free running model sea trial. This study also provides a scheme of ship vertical motion stabilization technique by using Semi-Submerged Bow (SSB) appendages. Firstly, an improved strip theory based 2.5D theoretical seakeeping algorithm, which considers the viscous flow effects attributed to bow appendages, is developed to estimate ship vertical motion responses in regular waves. Short-term predictions are also made on the basis of spectral analysis theory to predict ship motion responses in irregular waves. Then corresponding small-scale models are made and tested in a laboratory towing tank for both regular and irregular wave conditions to confirm the numerical results. The tank testing results between different ship schemes are also compared to experimentally investigate the effects of SSB and fin on hull vertical motion stabilization. Furthermore, large-scale model sea trials are conducted in coastal waves for a final validation of the ship seakeeping performance in short-crested sea waves. Finally, comparisons of the results by different testing approaches are systematically made and analyzed. Highlights: Ship motions obtained by improved strip theory, tank model test and large model sea trial are comparatively investigated. A scheme of Semi-Submerged Bow (SSB) was designed for ship vertical motion stabilization. An improved 2.5D seakeeping theory is developed to estimate vertical motion responses of ship with SSB. Large-scale free running model seakeeping tests were conducted in actual sea waves.